Comparative study of the interaction of buriedstructures with ground and superstructure using different approaches - Şişman, Rafet (My University, 2020)
Metro stations and tunnels are some of the crucial infrastructure systems for modern everyday life in big cities. Considering the seismic vulnerability of megacities such as Istanbul, the dynamic interaction effects on surface structures due to existence of these kind of underground structures are not thoroughly investigated. The aim of this thesis is to investigate the above mentioned interaction problem, i.e. the dynamic interaction effects on a surface structure due to existence of an underground structure. For this purpose two dimensional numerical models which utilizes Finite Element Method are generated and dynamic time history analyses are performed. Material non-linearity is only considered for the soil domain and the surface structure and underground structure are modelled as linear-elastic. The surface structure is modelled as a Single Degree of Freedom system with a mat foundation lying on the soil deposit. The underground structure is modelled as a frame structure which is embedded in the soil deposit. A Ricker wavelet with 1 Hz dominant frequency is used as input motion acceleration history for the numerical analyses. There are totally 3528 numerical models which correspond to combinations of seven different case parameters. The case parameters are; input motion amplitude, soil layer properties, underground structure depth ratio, underground structure height, underground structure wall thickness, surface structure lateral distance ratio and surface structure fundamental period. The numerical analyses results include surface structure acceleration and drift responses along with spectral responses of ground surface accelerations. Additionally, importance order for the case parameters are obtained by an Artificial Neural Network based sensitivity analysis. This thesis reveals that directly including the surface structure in the numerical model yields higher amplifications in the responses due to existence of underground structure. The surface structure responses may amplify or de-amplify depending on the distance between the surface structure and the underground structure.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Soil - structure interaction; Underground structures; Finite element method; Opensees; Zemin - yapı etkileşimi; Yer altı yapıları; Sonlu elemanlar yöntemi